2018
DOI: 10.1186/s40981-018-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Unusually large ephedrine-induced blood pressure increases due to cardiac sympathetic denervation supersensitivity in a patient with Parkinson’s disease

Abstract: Background: Parkinson's disease (PD) patients often suffer from cardiac sympathetic denervation, a hallmark of which is orthostatic hypotension. Denervation supersensitivity to sympathomimetic drugs is also seen in such patients, and this phenomenon is important and can be sometimes dangerous. Case presentation: A 65-year-old male underwent gastrojejunostomy. The patient had severe PD and did not exhibit metaiodobenzylguanidine (MIBG) accumulation in his heart, which was indicative of cardiac sympathetic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition, the fact that only the blood pressure increased and the heart rate did not change significantly is unusual, which is similar to the findings observed in the patients with Parkinson disease. [9,13] Therefore, we speculated that in the present case, a severe intraoperative reduction in the sympathetic pathway activity to the heart may have caused transient hypersensitivity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the fact that only the blood pressure increased and the heart rate did not change significantly is unusual, which is similar to the findings observed in the patients with Parkinson disease. [9,13] Therefore, we speculated that in the present case, a severe intraoperative reduction in the sympathetic pathway activity to the heart may have caused transient hypersensitivity.…”
Section: Discussionmentioning
confidence: 81%
“…[8] To determine the reason for the abnormal reaction to ephedrine administration in the present case, we referred to reports of ephedrine adverse reactions in patients with Parkinson disease. [9][10][11] These reports indicated that cardiac sympathetic nerve denervation can occur in patients with Parkinson disease, resulting in excessive cardiovascular responses to sympathomimetic drugs; this condition is known as cardiac sympathetic denervation supersensitivity. Its mechanism of action could be explained by an absence of norepinephrine uptake or an increased density of β-adrenergic receptors in postsynaptic membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac consequences of DAN manifest as damage to the nerve fibers that innervate the heart and blood vessels, resulting in abnormalities in HR dynamics, increased risk of arrhythmias, and potential for SCD 41 , 44 . Likewise, clinical evidence suggests that patients with Parkinson’s disease may have supra-physiologic cardiovascular responses to adrenergic stimulation 45 , 46 , but detailed investigations of cardiac electrophysiological responses in these patients have not been performed. We previously showed that aged hearts have significantly decreased ventricular sympathetic nerve density, ventricular NE content, and reduced responsiveness to SNS 47 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a case of unusually strong responses to ephedrine in a patient with PD under general anesthesia, which we thought was due to the sympathetic nerve denervation supersensitivity, because the patient’s sympathetic nerves to the heart were completely denervated [6]. However, to the best of our knowledge, there have been few other clinical reports on denervation supersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is often overlooked because it can only be detected when sympathomimetic agents are administered. However, anesthesiologists should be aware of this phenomenon because it can cause dangerous hemodynamic changes [46]. Here, we present a case of ephedrine-induced increases in blood pressure and heart rate suspected to be due to denervation supersensitivity in a patient with PD.…”
Section: Introductionmentioning
confidence: 98%